Predictors of Long‐Term Survival in Patients With Immune Checkpoint Inhibitor–Associated Myocarditis - Nikhil Dubey; Chia‐Yun Wu; Leyre Zubiri; Magdalena Fay; Sherin J. Rouhani; Ross D. Merkin; Joie Sun; Joseph J. Locascio; Tomas G. Neilan; Kerry L. Reynolds; Daniel A. Zlotoff (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Immune checkpoint inhibitor–associated myocarditis (ICIM) carries high rates of morbidity and death, but clinical outcomes vary widely. Little is known about the clinical variables associated with long‐term survival. Methods In this case–control study, patients diagnosed with ICIM at Massachusetts General Hospital between 2016 and 2022 were stratified into 3 groups based on length of survival after ICIM diagnosis: short‐term (<30 days), intermediate‐term (30–365 days), and long‐term (>365 days). Baseline characteristics, immune checkpoint inhibitor regimens, laboratory values, ECG parameters, and ICIM treatments were analyzed to identify predictors of long‐term survival. Results Among 35 patients with ICIM (median follow‐up time, 8.3 months), there were 9 (25.7%) in the short‐term survival group, 13 (37.1%) in the intermediate‐term survival group, and 13 (37.1%) in the long‐term survival group. Those in the short‐term survival group were older (median age, 82 versus 68 for intermediate‐term and 75 for long‐term; P=0.003). Using logistic regression, long‐term survival was associated with an interval from immune checkpoint inhibitor initiation to ICIM diagnosis ≥75 days (odds ratio, 5.4; P=0.043) and a troponin T decrement ≥42% by day 8 after immunosuppression initiation (odds ratio, 5.5; P=0.042). Using multivariate Cox regression modeling, troponin T≤1000 ng/L (hazard ratio [HR], 4.0; P=0.007) and neutrophil/lymphocyte ratio ≤4.4 (HR, 7.9; P < 0.001) were independently associated with longer survival. Conclusions Time to onset of ICIM, multiple clinical tests, and responsiveness to immunosuppressive therapy were associated with long‐term survival after ICIM. Consideration of these variables may help with risk stratification and immunosuppressive therapy individualization.